The Local Tradition of Gorontalo and Health Anthropology: Gorontalo’s Experience in Addressing the COVID-19 Pandemic - Tanipu, Funco (Poltekkes Kemenkes Palu, 2024)
This paper explores the overlapping consensus between indigenous kinship practices and the spread of diseases. The COVID-19 pandemic has altered the community’s way of life and behaviour, yet Gorontalo’s indigenous kinship-based traditions contradict the implemented health protocols. Due to their foundation in the kinship system (ngala’a), these traditions necessitate everyday interactions among individuals. The clash between local traditions and health procedures leads to the widespread transmission of Covid-19. This research argues that relying on Gorontalo’s traditions would increase the likelihood of community exposure to COVID-19, as shown by descriptive analysis. Therefore, it is fundamental to reassess the significance of traditions during the Covid-19 pandemic.